Stephen Reckert, Beyond chrysanthemums: Perspectives on poetry East and West. Clarendon Press, Oxford, 1993; 271 pp. - Pedrosa, José Manuel (Nueva Revista de Filología Hispánica (NRFH), 1998)
Se reseñó el libro: Beyond chrysanthemums: Perspectives on poetry East and West.